ICT Indicators and Implications for Methods for Assessing Socioeconomic Impact of ICT - World Bank (Washington, DC, 2014)
This report is being delivered pursuant to the agreement (Agreement) between the Ministry of Communications and Information Technology of the Arab Republic of Egypt (MCIT) and the World Bank (Bank) for the provision by the Bank of technical assistance (RTA) to MCIT and certain of its affiliates. One of those affiliates is the Information Technology Industry Development Authority (ITIDA). When it comes to designing and implementing ICT policies, the availability of proper indicators is key to efficiency and effectiveness. However, the indicators should go further, and should help policymakers also to measure how well the sector or projects are performing, provide an assessment over time on the status of a project, program, or policy, promote credibility and public confidence by reporting on the results of programs, provide in-depth information about public sector performance, help formulate and justify budget requests, and identify potentially promising programs or practices for duplication or scalability. Thus, this report is composed of the following sections: (i) a discussion of indicator types, in particular impact indicators and their constraints; (ii) an overview of the institutional setup of ICT data in Egypt; (iii) ICT data categories and methodologies used by major international indices and reports, including an analysis of Egypt's strong and weak results in the indices; (iv) a mapping and gap analysis between the indices' indicators and those currently collected by Egypt; (v) a set of recommendations for Egypt and (vi) implications of this work with respect to analyzing the socioeconomic impact of ICTs on investment, trade, growth and education in Egypt.